The Choice of a Rational Technology for Manufacturing the Hydrogenerators-Motors Rotor Rim - Pavlo M. Makarov (Journal of Mechanical Engineering, 2023)
The object of research in the paper is the technology of manufacturing segments of the rotor rim of large hydrogenerators-motors. The subject of study is the design and geometrical state of the rotor rim during the operation of hydraulic units. The goal is to make a three-dimensional mechanical calculation of the rotor segment for the further determination of the most optimal technology for the rotor rim manufacturing. The following tasks are set: to study the peculiarities of the manufacturing technology of the rotor rim segments; to perform an analytical calculation and a three-dimensional calculation with the determination of the average values of stresses and deformations in the rotor segment. The used methods are: finite element method of mathematical modeling of the thermal stress state of nodes. The following results were obtained: a description of the two main manufacturing technologies of the rotor rim segments, namely the stamping method and the laser cutting method, was provided. The advantages and disadvantages of each technological process were analyzed, and it was determined that the laser cutting method should be used in the production of powerful small-scale hydrogenerators. Three-dimensional models of the rotor segment were developed and a three-dimensional mechanical calculation of this model was performed, as a result of which the value of the displacement of the rotor of the hydrogenerator at the nominal frequency of rotation, as well as the average values of the stresses in the spoke and the rim of the rotor, were obtained. Based on the results of calculations, it was established that significant tolerances in the manufacture of rotor segments can lead to changes in the shape of the rotor during its further operation, the appearance of additional vibrations and further affect the performance of the hydraulic unit. The scientific novelty consists in a combined approach to the estimation of the average values of stresses and deformation of the rotor rim, taking into account the technology of its manufacture, which includes elements of analytical mechanical calculation and calculation in a three-dimensional setting.